1974
DOI: 10.1073/pnas.71.12.4792
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Production Accompanies Loss of Anchorage Regulation in Transformation of Primary Rat Embryo Cells by Simian Virus 40

Abstract: We have isolated several lines of rat embryo cells transformed by simian virus 40. All these lines are fully transformed with regard to saturation density and serum sensitivity, but they differ greatly in their anchorage dependence, as assayed by efficiency of plating in methyl cellulose suspension. This set of lines reveals a consistent relation of plasminogen activator production to plating efficiency in methyl cellulose. T-antigen-positive transformed lines that synthesize activator grow in methyl cellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 34 publications
4
69
0
Order By: Relevance
“…This problem has previously been partially addressed by Pollack's group who infected mouse 3T3 or rat embryo fibroblasts with SV40 and isolated cell lines with the minimal possible preselection, i.e., random single-cell cloning (50,56). From these experiments they concluded that infection of cells by SV40 can result in either (i) full transformation in which the cells grow in low serum, are anchorage independent, and are tumorigenic within a short latency period, less than 4 weeks; or (ii) minimal transformation in which the cells express T antigen, grow in low serum, are established, but are not anchorage independent for growth (50,56). They also found that it was possible to isolate full transformants from the minimal transformants by selection for anchorageindependent growth in methyl cellulose or tumor formation in a BALB/c nude mouse (64).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This problem has previously been partially addressed by Pollack's group who infected mouse 3T3 or rat embryo fibroblasts with SV40 and isolated cell lines with the minimal possible preselection, i.e., random single-cell cloning (50,56). From these experiments they concluded that infection of cells by SV40 can result in either (i) full transformation in which the cells grow in low serum, are anchorage independent, and are tumorigenic within a short latency period, less than 4 weeks; or (ii) minimal transformation in which the cells express T antigen, grow in low serum, are established, but are not anchorage independent for growth (50,56). They also found that it was possible to isolate full transformants from the minimal transformants by selection for anchorageindependent growth in methyl cellulose or tumor formation in a BALB/c nude mouse (64).…”
mentioning
confidence: 99%
“…The resulting variation in levels of viral mRNA and gene expression can significantly affect the range of phenotypes of the transformants. Previous studies of the variation in phenotype observed after transformation by SV40 detected clonal cell lines that ranged over completely, partially, or minimally transformed (50,56).…”
mentioning
confidence: 99%
“…The factors necessary for the migration of smooth muscle cells are not known but there are limited data to suggest a role for plasminogen activators (PAs) in this process. PAs are thought to play a major role in cancer, especially in facilitating the metastasis of cancer cells via the generation of plasmin which has a relatively broad specificity for catabolism of matrix molecules.2 8 , [44][45][46] We have shown that tissue plasminogen activator (tPA) activity is increased in balloon catheter-injured arteries and others have shown upregulation of both urokinase (uPA) and tPA expression following arterial injury (Figure 8). 47 Of interest to us is the finding that bFGF is known to stimulate expression of tPA and as described above we now know that bFGF is released from injured arteries.…”
Section: Control Of Smooth Muscle Cell Migrationmentioning
confidence: 99%
“…PA synthesis and secretion have been shown to be elevated in human neoplastic cells (Camiolo et al, 1981 ;Corasanti et aL, 1980;Evers et al, 1982;Markus et al, 1980;Nagy et al, 1977;Recklies et al, 1980;Tucker et al, 1978 ;Wilson & Dowdle, 1978;Wilson et al, 1980), in cells transformed by oncogenic viruses (Unkeless et al, 1973(Unkeless et al, , 1974Ossowski et al, 1973Ossowski et al, , 1974Christman & Acs, 1974;Pollack et al, 1974;Adelman et al, 1980) and chemicals, and in many tumorigenic cell lines (for reviews see Reich, 1975;Rifkin et al, 1975;Brynes et al, 1980;Quigley et al, 1980). The early appearance of this enzymatic activity during in vitro cell transformation has been demonstrated through the use of virus mutants that are temperature-sensitive for transformation (Unkeless et al, 1973).…”
Section: Introductionmentioning
confidence: 99%